Germination and development of ornamental sunflower seedlings in substrates - Dos Santos, Patrick Luan Ferreira; De Castilho, Regina Maria Monteiro [UNESP] (Lepidus Tecnologia, 2018)
The ornamental sunflower is a growing crop in recent years due to its rapid return on investment and expressive representation in the flower market, and research on the ideal substrate for seedling production is essential to maximize information for the crop. Thus, the objective was to evaluate the germination and development of ornamental sunflower seedlings in different substrates compositions. The experiment was installed in a greenhouse, where they were put to germinate, seeds of sunflower type Vincent's Choice in poliestileno trays on substrates with or without addition Slow Release Fertilizer (SRF) at the dose 2 g L -1 . The experimental design was completely randomized with 4 treatments [T1- Charcoal + pine bark + peat + expanded vermiculite (1:1:1:1), T2- Coconut fiber + carbonized rice hull + peat + expanded vermiculite (1:1:1:1), T3- Charcoal + pine bark + peat + expanded vermiculite (1:1:1:1) + SRF, T4- Coconut fiber + Carbonized rice hull + peat + expanded vermiculite (1:1:1:1) + SRF] with 8 replicates of 8 seeds, totaling 64 seeds per substrate. It was evaluated: the percentage, index and average germination time, chlorophyll content, length, fresh and dry mass of shoot and root. It was observed that there was no difference in the percentage of germination, but T2 and T4 promoted emergency in the lowest mean time (3.19 and 3.46 days, respectively) with a higher rate of velocity (2.43 and 2.25 respectively), still, T4 presented increments with more than 50% of fresh and dry mass. Thus, it is concluded that the T4 substrate is recommended for germination and development of ornamental sunflower type Vicent's Choice.

O girassol ornamental é uma cultura crescente nos últimos anos devido ao seu rápido retorno de investimento e expressiva representação no mercado de flores, e pesquisas referentes ao substrato ideal para produção de mudas é essencial para maximizar as informações para a cultura. Assim objetivou-se avaliar a germinação e desenvolvimento de plântulas de girassol ornamental em diferentes composições de substratos. O experimento foi instalado em casa de vegetação, onde foram postas para germinar, sementes de girassol tipo Vicent's Choice, em bandejas de poliestileno, em substratos acrescidos ou não de Adubo de Liberação Lenta (ALL) na dose de 2 g L -1 . o delineamento experimental foi inteiramente casualisado sendo 4 tratamentos [T1- Carvão vegetal + casca de pinus + turfa + vermiculite expandida (1:1:1:1), T2- Fibra de coco + casca de arroz carbonizada + turfa + vermiculita expandida (1:1:1:1), T3- Carvão vegetal + casca de pinus + turfa + vermiculita expandida (1:1:1:1) + ALL, T4- Fibra de coco + casca de arroz carbonizada + turfa + vermiculita expandida (1:1:1:1) + ALL)] com 8 repetições de 8 sementes, totalizando 64 sementes por substrato. Avaliou-se: porcentagem, índice e tempo médio de germinação, teor de clorofila, comprimento, massa fresca e seca da parte aérea e da raiz. Observou-se que não houve diferença na porcentagem de germinação, porém, T2 e T4 promoveram emergência em menor tempo médio (3,19 e 3,46 dias, respectivamente) com maior índice de velocidade (2,43 e 2,25 respectivamente), ainda, T4 apresentou incrementos com mais de 50% de massa fresca e seca. Assim, conclui-se que o substrato T4 é o recomendado para germinação e desenvolvimento de girassol ornamental tipo Vicent's Choice.
Keywords: Adubo de liberação lenta; Helianthus annuus; Produção de mudas; Seed vigor; Seedling production; Slow release fertilizer; Vigor de sementes